2013
DOI: 10.7860/jcdr/2012/4794.2687
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sevista in the Management of Dysfunctional Uterine Bleeding

Abstract: Objective: The complaints of excessive menstrual bleeding (menorrhagia) have a substantial impact on the gynaecological services and in most of the cases, no organic pathology is identified. Nonsteroidal anti-inflammatory drugs and tranexamic acid offer a simple therapy which has to be taken during menses, with reductions of 25-35% and 50% respectively in the Menstrual Blood Loss (MBL). Danazol and the gonadatrophin-releasing hormone analogues are highly effective, but their side-effects make them suitable onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
5
7
0
Order By: Relevance
“…The results suggested that there is a significant increase in Hb level ( P < 0.0001) and decrease in ET ( P < 0.0001) as because ormeloxifene has anti-proliferative effect on endometrium which causes endometrial atrophy leading to decrease in menstrual blood loss. Our study is in accordance with Bs and Nanda[11] and also with Kriplani et al .,[9] where they have found a significant rise in Hb level and decrease in ET. Grover et al .…”
Section: Discussionsupporting
confidence: 93%
“…The results suggested that there is a significant increase in Hb level ( P < 0.0001) and decrease in ET ( P < 0.0001) as because ormeloxifene has anti-proliferative effect on endometrium which causes endometrial atrophy leading to decrease in menstrual blood loss. Our study is in accordance with Bs and Nanda[11] and also with Kriplani et al .,[9] where they have found a significant rise in Hb level and decrease in ET. Grover et al .…”
Section: Discussionsupporting
confidence: 93%
“…Similar to the present study, Dhananjay et al found a statistically significant increase in hemoglobin concentration (8.26 to 10.59g/dl; p<0.001) and a statistically significant decrease in the endometrial thickness (8.36 to 4.89mm; p<0.001) after 3 months of treatment with ormeloxifene [8].…”
Section: Discussionsupporting
confidence: 90%
“…Amenorrhea was a common symptom seen in different studies with a wide range of 8% to 42.9% [3][4][5]8,9]. It is more common in perimenopausal women However, with proper counseling the women do not find it bothersome, in fact it is welcomed by them.…”
Section: Discussionmentioning
confidence: 99%
“…Present study shows ET reduction of 3.33 mm in control group while 2.44 mm in study group, which is comparable with other studies. [10][11][12][13][14] Our data shows comparable results for reduction of endometrial thickness in both control group as well as study group and also comparable with other studies. It proves that 30mg of ormeloxifene is as effective as 60mg of ormeloxifene in treatment of DUB when effectiveness of treatment assessed in form of reduction of endometrial thickness.…”
Section: Discussionsupporting
confidence: 79%
“…(8.26 to 10.59gm%; p<0.001). 12 In a study by Biswas et al mean rise in hemoglobin after treatment was 1.31gm% (9.42 to 10.73gm%; p<0.001). 11 In a study by Neha et al mean rise in hemoglobin was 2.88gm% (7.52 to 10.4gm%).…”
Section: Discussionmentioning
confidence: 99%